3-D Multi-Input Multi-Output (MIMO) Pulsed Chaos Lidar Based on Time-Division Multiplexing - Chen, Jun-Da; Wu, Kuan-Wei; Ho, Hsin-Lin; Lee, Cheng-Ting; Lin, Fan-Yi (IEEE journal of selected topics in quantum electronics, 2022)
In this study, we propose and evaluate a 3D multi-input multi-output (MIMO) pulsed chaos lidar based on time-division multiplexing. By time-gating a chaos waveform sequentially at different times, chaos-modulated pulses for different channels that are uncorrelated with each other can be generated. To quantitatively evaluate the anti-interference/jamming capability, we investigated the detection performance of the MIMO chaos lidar under different jamming strengths and overlapped ratios between the jamming and the signal pulses. The overall detection probabilities of the chaos lidar and a conventional time-digital-converter-based pulsed lidar under the influence of interference/jamming were compared and we found that the chaos lidar exhibits strong resistance to the interference/jamming. Employing the 3D MIMO chaos lidar developed, we demonstrate 3D imaging under the influence of interference/jamming. By simultaneously scanning 2 different channels with overlapped field-of-views (FOVs), 3D images with large-FOV/low-resolution and small-FOV/high-resolution were obtained at the same time.